2012
DOI: 10.15376/biores.7.4.5181-5189
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Polyethylene-Based Composites With Pressure-Treated Wood Fibers

Abstract: High-Density Polyethylene (HDPE)-based composites with alkaline copper quaternary (ACQ)-and micronized copper quaternary (MCQ)-treated wood fibers were manufactured through injection molding. The mechanical properties, water absorption, and biological resistance properties of the fabricated composites with different coupling treatments were investigated. Composites with ACQ-and MCQ-treated wood had mechanical properties comparable with those made of untreated wood. The different coupling agents worked well for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…These findings imply that the CSF content is an important factor affecting the degradation behavior of CSF/HDPE composites infected by the mixed soft rot fungal inocula. Our data is in agreement with the results described in earlier publications [ 13 , 24 ]. As expected, there were significant differences in the mass loss between CSF/HDPE and the poplar wood control sample.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…These findings imply that the CSF content is an important factor affecting the degradation behavior of CSF/HDPE composites infected by the mixed soft rot fungal inocula. Our data is in agreement with the results described in earlier publications [ 13 , 24 ]. As expected, there were significant differences in the mass loss between CSF/HDPE and the poplar wood control sample.…”
Section: Resultssupporting
confidence: 94%
“…Termite resistance increased 2.6- and 1.2-fold at an ACQ level of 3% for the 50/50 and 60/40 formulations, respectively. Shang et al [ 13 ] also reported that termite resistance increased by approximately three-fold at an ACQ level of 4% for the 40/60 (wood/plastic) formulation. The increase in termite resistance was smaller for the ZB treatment than for the ACQ treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pendleton et al (2002) found that biological resistance was exhibited in the wood/high-density polyethylene (HDPE) composites containing ZB. Stable mechanical properties, similar moisture sorption behaviors, and improved biological performances were shown in the HDPE-based composites treated with ACQ and micronized copper quaternary, as reported by Shang et al (2012). Similarly, Tascioglu et al (2013) reported that addition of ZB at a 1% retention level decreased the mass loss of WPCs when exposed to laboratory decay and termite tests.…”
Section: Introductionsupporting
confidence: 67%
“…Previous studies on the use of CCA-treated wood in WPCs have been very limited. 7,8 In this study, recycled CCA-treated wood was used as a filler to produce WPCs. The effects of the coupling agent and filler content on the water absorption, thickness swelling, mechanical and thermal properties, biological performance and morphology of the WPCs were investigated.…”
Section: Introductionmentioning
confidence: 99%